2019
DOI: 10.1093/biolre/ioz094
|View full text |Cite
|
Sign up to set email alerts
|

Role of activin, follistatin, and inhibin in the regulation of Kiss-1 gene expression in hypothalamic cell models†

Abstract: Kisspeptin (encoded by the Kiss-1 gene) in the arcuate nucleus (ARC) of the hypothalamus governs the hypothalamic-pituitary-gonadal (HPG) axis by regulating pulsatile release of gonadotropin-releasing hormone (GnRH). Meanwhile, kisspeptin in the anteroventral periventricular nucleus (AVPV) region has been implicated in estradiol (E2)-induced GnRH surges. Kiss-1–expressing cell model mHypoA-55 exhibits characteristics of Kiss-1 neurons in the ARC region. On the other hand, Kiss-1 expressing mHypoA-50 cells orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, immunization against FST significantly upregulated Gnrh1 and Gnih mRNA levels from the hypothalamus. In vitro studies had shown that activin A might act at the hypothalamus in mice and activate the secretion of GnRH by modulating Kiss1 gene expression, whereas FST reduced Kiss1 gene expression and abolished activin’s effect on the Kiss1 gene [ 43 ]. More studies are needed to understand these findings in birds.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunization against FST significantly upregulated Gnrh1 and Gnih mRNA levels from the hypothalamus. In vitro studies had shown that activin A might act at the hypothalamus in mice and activate the secretion of GnRH by modulating Kiss1 gene expression, whereas FST reduced Kiss1 gene expression and abolished activin’s effect on the Kiss1 gene [ 43 ]. More studies are needed to understand these findings in birds.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study using a hypothalamic Kiss-1-expressing cell model, mHypoA-55 cells, we reported that exogenous activin increased Kiss-1 expression, whereas inhibin A and follistatin decreased its expression [ 13 ]. Our present study confirmed that these gonadal factors had similar effects on Kiss-1 gene expression when we used a more physiological neuronal cell model obtained from fetal rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this report, it is possible that Kiss-1 neurons from the AVPV region of the hypothalamus were absent from our primary neuronal cells, and that the phenomena observed in this study occurred only in Kiss-1 neurons in the ARC region of the hypothalamus. In this regard, we reported previously that activin, inhibin A, and follistatin stimulation do not modify Kiss-1 expression in the mHypoA-50 cell model, which originated from hypothalamic neurons in the AVPV region [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LβT2 cells (kindly provided by Dr. P. Mellon of the University of California, San Diego, CA) and GH3 cells (CCL-82.1, American Type Culture Collection) were plated in 35-mm tissue culture dishes and incubated with high-glucose Dulbecco's modified Eagle's medium (Sigma-Aldrich Co.) containing 10% heatinactivated foetal bovine serum and 1% penicillin-streptomycin at 37 °C under a humidified atmosphere of 5% CO 2 in air. For the stimulation experiments, the medium was changed to high-glucose Dulbecco's modified Eagle's medium containing 1% heat-inactivated foetal bovine serum and 1% penicillin-streptomycin, and the cells were incubated without (control) or with the test reagents (DHT, activin A, inhibin A, and TRH) for 24 h. e concentration and stimulation times of DHT, activin A, and inhibin A were chosen because we already knew that these concentrations and stimulation times cause cultured hypothalamic cells to change their characteristics [21,22].…”
Section: 21mentioning
confidence: 99%